P–441 Semen quality and cryopreservation in adolescent transgender females. (6th August 2021) - Amir, H; Perl, L; Barda, S; Lantsberg, D; Sege. Becker, A; Israeli, G; Azem, F; Oren, A
Abstract: Study question: What are the semen quality and cryopreservation outcomes among adolescent transgender females at the time of fertility preservation (FP) before initiating gender-affirming hormone (GAH) treatment? Summary answer: Semen quality is strongly reduced among adolescent transgender females before hormone therapy and their stored sperm samples are suitable for intracytoplasmic sperm injection (ICSI). What is known already: The age of individuals seeking treatment for gender affirmation has fallen sharply in recent years and many of them are adolescents. Estrogen, the primary treatment for transgender women, is known to impair semen quality and fertility potential. Sperm cryopreservation enables young transgender females to circumvent GAH therapy-related fertility impairment and have genetically related children. There are recent data on semen quality among adult transgender women who preserve fertility before exposure to GAH therapy, but little is known about pubertal transgender female adolescents. Study design, size, duration: This retrospective cohort study included 26 adolescent transgender females who underwent FP between June 2013 and October 2020. Participants/materials, setting, methods: Before initiating gonadotropin-releasing hormone agonists solely or with GAH treatment, 25 adolescent transgender females were referred to FP in our Fertility Institute of a tertiary university-affiliated medical center. Pre-freezing semen parameters were compared to WHO 2010 reference values. Post-thaw semen parameters were used to determine adequate assisted reproductive technology (ART). A multivariate linear regression analysis was performed to assess the impact of selected medical and lifestyle factors on the semen quality of our study participants. Main results and the role of chance: The mean age at which adolescent transgender females underwent sperm cryopreservation was 16.2 ± 1.38 years. The median values of all semen parameters in our study group were significantly lower compared to the WHO data on semen quality in the general population of unscreened men, including volume (1.46 ml vs 3.2 ml, respectively, P = 0.001 ), sperm concertation (28*106/ml vs 64*106/ml, P < 0.001), total sperm number (28.2*106 vs 196*106, P < 0.001), total motility (51.6% vs 62%, P < 0.001), and normal morphology (2% vs 14%, P < 0.001). The frequency of semen abnormalities was teratozoospermia 72%, hypospermia 52%, oligozoospermia 28%, and azoospermia 4%. The median post-thaw total motile count was 0.17*106 per vial, and the quality was adequate only for ICSI in 87.7% of the thawed semen samples. Attention-deficit/hyperactivity disorder (ADHD) diagnosis, history of depression/anxiety, medication for ADHD, and antidepressant drugs were found to correlate with hypospermia. No correlation was found between the time of FP, body mass index, autistic spectrum disorder diagnosis, cannabis use, testis tucking, or the levels of follicle-stimulating hormone, estradiol, and testosterone on the semen parameters. Limitations, reasons for caution: Because no normal values of semen in adolescents are available and the absence of a matched control group, we used WHO 2010 semen data as reference values, and they may not be representative of the adolescent population. Wider implications of the findings: Although adolescent transgender females have poor semen quality and limited stored semen samples suitable for advanced ART interventions, even before starting GAH therapy, we highly recommend sperm cryopreservation before initiating GAH treatment and thereby prevent further impairment of sperm quality associated with the hormonal treatment. Trial registration number: Not applicable